High-mobility band-like charge transport in a semiconducting two-dimensional metal–organic framework. Issue 11 (November 2018) - Dong, Renhao; Han, Peng; Arora, Himani; Ballabio, Marco; Karakus, Melike; Zhang, Zhe; Shekhar, Chandra; Adler, Peter; Petkov, Petko; Erbe, Artur; Mannsfeld, Stefan; Felser, Claudia; et al.
Abstract Metal–organic frameworks (MOFs) are hybrid materials based on crystalline coordination polymers that consist of metal ions connected by organic ligands. In addition to the traditional applications in gas storage and separation or catalysis, the long-range crystalline order in MOFs, as well as the tunable coupling between the organic and inorganic constituents, has led to the recent development of electrically conductive MOFs as a new generation of electronic materials. However, to date, the nature of charge transport in the MOFs has remained elusive. Here we demonstrate, using high-frequency terahertz photoconductivity and Hall effect measurements, Drude-type band-like transport in a semiconducting, π–d conjugated porous Fe3 (THT)2 (NH4 )3 (THT, 2, 3, 6, 7, 10, 11-triphenylenehexathiol) two-dimensional MOF, with a room-temperature mobility up to 220 cm2 V–1 s–1 . The temperature-dependent conductivity reveals that this mobility represents a lower limit for the material, as mobility is limited by impurity scattering. These results illustrate the potential for high-mobility semiconducting MOFs as active materials in thin-film optoelectronic devices. Semiconducting metal–organic frameworks (MOFs) can be of interest for optoelectronics, but charge transport property is rarely elucidated. Here, a π–d conjugated 2D MOF shows band-like charge transport, with room-temperature mobility of 220 cm2 V–1 s–1 .